WAJAH STUDI ALQURAN DI JERMAN AKHIR ABAD KE-20: TERJEMAHAN ALQURAN RUDI PARET DAN BEBERAPA PEMIKIRANNYA - Qadafy, Mu?ammar Zayn (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2017)
To investigate wriggles of Qur?anic studies at Germany in the end of 20th Century, one should examine works of its influential figure, such as Rudi Paret who was broadly considered as the most intelligent student of Enno Littman, a veteran German orientalist. This article describes and discusses the contribution of Paret?s works along with its methodological strength and fragility based on reviews written by their observers. The results of the passage will be used to map Paret thought, both about Islam and the Qur?an. It is concluded that: first, Paret?s research on the Qur?an contributes a lot to the development of the Qur?anic interpretation methodology; and second, Der Koran: Kommentar und Konkordanz is a work of interpretation based on the translation methodology, in which the text of the Qur?an is understood and explained by something parallel. This method resulted in a ?concordance?, Paret?s concrete offer to stand against the chronological reading of the Qur?an that developed rapidly in his days.